Unraveling the Diagnostic Challenge of Arachnoiditis Ossificans in Association with Syringomyelia: A Review of the Literature and Two Case Reports - Khafaji, Fatemeh; Tuettenberg, Jochen; Sommer, Clemens; Reyes Medina, Bernardo; Hertel, Frank (Journal of Neurological Surgery Reports, 2025)
Arachnoiditis ossificans (AO) associated with syringomyelia (SM) is a rare pathology. Its clinical and image-based diagnostic features are challenging to identify. Only a limited number of cases have been published thus far. We present two new cases and offer a review of the literature.We conducted a systematic literature search using PubMed, Web of Science, and Google Scholar with the following keywords: Arachnoiditis ossificans, leptomeningeal calcification, and spinal meningeal calcification, in combination with syrinx, syringomyelia, hydromyelia, cord cavitation, and cystic necrosis of the spinal cord.AO-SM predominantly affected females (12 F, 7 M), with a mean age of 55.84 ± 14.7 years. The mean follow-up was 14.07 ± 9.01 months postoperatively. The main complaints included low back pain and progressive para-/tetraparesis, with or without urinary disturbances. Potentially causative events occurred 25.07 ± 13.75 years prior to diagnosis. Based on imaging findings, patients primarily experienced thoracic AO-SM. In seven studies, arachnoid cysts were reported in association with AO-SM. Surgical treatment mainly involved microsurgical AO resection, shunting, or draining of the SM, along with duraplasty and cystectomy or fenestration of the arachnoid cyst. A second surgical intervention was conducted on five patients. Approximately 57% of the patients showed improvement.AO-SM remains one of the least understood causes of myelopathy. Clinical and imaging diagnostics continue to pose challenges. Preoperative evaluation using magnetic resonance imaging (MRI) and native CT may be regarded as the gold standard. CT myelography and, occasionally, Cine MRI should be considered to determine the best surgical option. Surgical treatment continues to be a dilemma.
Keywords: arachnoiditis ossificans; CSF block; syringomyelia